The republican exile in the light of Juan Negrín’s memory - Grillo, Sabrina (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2018)
The last republican head of government during the civil war of Spain, Juan Negrín, had to manage the republican exile. Conscious since the autumn of 1938 of the weaknesses of the Republic to defeat the Francoists, initiated a process whose goal was to use part of the wealth of the Republic to meet the needs of refugees in Mexico. The republican exile to Mexico caused a multilateral division. Some of the origins of the political divisions are exposed here and how Negrín referred to the end of the war in some manuscripts that are part of his memories.